(untitled) (REMUNOM, 2023)
The characterization, development and biomedical applicability of chitosan-based biomaterials in the regeneration of tissues damaged by disease and/or injury is a growing topic of scientific research. Chitosan is a linear biopolymer, derived from chitin, which has various therapeutic properties, with a strong emphasis on its antimicrobial potential. In addition, this biopolymer can be combined with other drugs that can enhance its pharmacological effects, such as essential oils rich in thymol and carvacrol. The aim of this study was to verify in the literature the efficacy of the association between biomaterials based on chitosan and essential oils from Thymus vulgaris L. and Origanum vulgare L. as an alternative therapy to combat oral infections. This is a narrative literature review with a documentary and observational approach. Several studies available in the literature show that chitosan-based biomaterials impregnated with essential oils potentiate antimicrobial activity against different microorganisms. In addition to promoting synergistic effects when associated with biomaterials, essential oils can cooperate with biopolymers during the manufacture of scaffolds or membranes. In view of the pre-existing literature, it is clear that the association between chitosan-based biomaterials and products of natural origin, such as the essential oils of Thymus vulgaris L. and Origanum vulgare L., could be an important alternative in the treatment of oral infections, as this is a low-cost and accessible option.